2022
DOI: 10.1021/acsami.2c05324
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Oxyfluoride Ceramic with In Situ Exsolved Ni–Fe Nanoparticles for Direct CO2 Electrolysis in Solid Oxide Electrolysis Cells

Abstract: Solid oxide electrolysis cell (SOEC) is a potential technique to efficiently convert CO 2 greenhouse gas into valuable fuels. Thus, there is significant interest in developing highly active and stable electrocatalysts for the CO 2 reduction reaction (CO 2 RR). Herein, a Ni and F co-doping strategy is proposed to facilitate the exsolution reaction and form a new cathode, Ni−Fe alloy nanoparticles embedded in ceramic Sr 2 Fe 1.5 Mo 0.5 O 6−δ (SFM) doped with fluorine. F-doping and Ni−Fe exsolution enhance CO 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 50 publications
(108 reference statements)
1
35
0
Order By: Relevance
“…From Figure e, it can be seen that the oxygen on the surface of R-PSCFM can be divided into three categories at around 531.4, 529.9, and 528.7 eV corresponding to surface oxygen species (O surf ), adsorbed oxygen species (O ads ), and lattice oxygen (O latt ), respectively. It has been demonstrated that O ads is closely correlated to oxygen vacancies, and the higher the O ads content, the higher the amount of oxygen vacancies. , Therefore, as shown in Figure f, the order of oxygen vacancy content is R-PSCFM-1 > R-PSCFM-2 > R-PSCFM-4 > R-PSCFM-3.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…From Figure e, it can be seen that the oxygen on the surface of R-PSCFM can be divided into three categories at around 531.4, 529.9, and 528.7 eV corresponding to surface oxygen species (O surf ), adsorbed oxygen species (O ads ), and lattice oxygen (O latt ), respectively. It has been demonstrated that O ads is closely correlated to oxygen vacancies, and the higher the O ads content, the higher the amount of oxygen vacancies. , Therefore, as shown in Figure f, the order of oxygen vacancy content is R-PSCFM-1 > R-PSCFM-2 > R-PSCFM-4 > R-PSCFM-3.…”
Section: Resultsmentioning
confidence: 86%
“…It has been demonstrated that O ads is closely correlated to oxygen vacancies, and the higher the O ads content, the higher the amount of oxygen vacancies. 11,31 Therefore, as shown in Figure 5f, the order of oxygen vacancy content is R-PSCFM-1 > R-PSCFM-2 > R-PSCFM-4 > R-PSCFM-3.…”
Section: Resultsmentioning
confidence: 91%
“…The O 1s spectra of the fresh and used catalysts are deconvoluted into two peaks. The peak at 530.7 eV represents lattice oxygen (O L ), and the higher binding energy at 532.8 eV corresponds to surface oxygen species (O S ), including O 2 2– , O – , hydroxyl, and carbonates, and so on (Figure d). ,,, The ratios of O S /O L are 12.2 and 9.3 for the fresh and used Nb 2 O 5 /SiO 2 catalysts, respectively. After the DMSO degradation reaction, the contents of lattice oxygen increased and the contents of surface oxygen species decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the NiFe nanoparticles facilitated the gas dissociation processes. Besides, Li and coworkers 23 synthesized the nonstoichiometric Zhang et al 24 proposed a Ni and F co-doping strategy and prepared the A-site deficient double perovskite Sr 1.9 Fe 1.5 Mo 0.4 -Ni 0.1 O 6Àd F 0.1 (SFMNi-F). The A-site deficiency suppressed the Sr segregation and stabilized the matrix phase.…”
Section: In Situ Exsolutionmentioning
confidence: 99%
“…Zhang et al 24 proposed a Ni and F co-doping strategy and prepared the A-site deficient double perovskite Sr 1.9 Fe 1.5 Mo 0.4 Ni 0.1 O 6− δ F 0.1 (SFMNi-F). The A-site deficiency suppressed the Sr segregation and stabilized the matrix phase.…”
Section: Anodementioning
confidence: 99%